Only one earth; the care and maintenance of a small planet - Ward, Barbara; Dubos, René J.; United Nations Conference on the Human Environment, Stockholm, 1972 (New York : Norton, 1972)
This is an unofficial report commissioned by the Secretary-General of the United Nations Conference on the Human Environment, prepared with the assistance of a 152-member committee of corresponding consultants in 58 countries.
lje 16/05/2018
Loans
Keywords: Human ecology